Regional circulation differences between a rainy episode and a nonrainy episode in eastern São Paulo State in March 2006 - Satyamurty, Prakki (2008)
The differences between the regional flow characteristics of a rainy episode and a nonrainy episode in March 2006 in eastern São Paulo state are discussed. The surface humidity and temperature characteristics do not show significant differences between the two cases. The composites of the middle tropospheric geopotential field and the lower-tropospheric wind field show a short-wave trough in the Atlantic off southern Brazil during the rainy episode. In the upper troposphere, the Bolivian high is stronger during the rainy episode than during the nonrainy episode, indicating that the troposphere over tropical South America is warmer during the rainy episode. The low-level jet in the rainy case does not penetrate northern Argentina, and is more NW-SE oriented, indicating that the humidity transport is more toward the southeastern Brazil. The moisture flux convergence over the eastern São Paulo at the 850-hPa is fairly strong in the rainy case whereas it is divergent in the nonrainy case. The presence of a low pressure area in the South Atlantic with westward tilt in the vertical provides synoptic forcing for the rising motion over eastern São Paulo state. These differences seem to be useful indicators for distinguishing rainy and nonrainy episodes.